Evaluation of Coordination and Coupling Degree of Cross-Regional Influence of the Construction Industry Based on Regional Economic Factors: A Case Study of Beijing, Capital of China - Likun Zhao; Yanqi Liu; Liwen Chen; Junsen Tian (Discrete Dynamics in Nature and Society)
Taking Beijing as the core, this study takes the data related to the construction industry from 2011 to 2018 as the basis. By constructing a cross-regional influence model and collaborative coupling evaluation model of China’s construction industry considering economic, social, and ecological development, this study comprehensively investigates the current situation of the cross-regional development of China’s capital construction industry. Results show that the external contribution of Beijing’s construction industry is manifested in three situations. A general trend of rising first and then falling is also observed. The contribution of Beijing’s construction enterprises to northwest China has long been low, whereas its contribution rate to Tianjin, Hebei, and Guangdong Provinces is high. The regional difference is significant, showing a “catch-up effect.” The contribution degree and the development level of China’s construction industry are usually at a low coupling and antagonistic level. The verification of the influencing factors indicates that the external influence of the construction industry in Beijing has a significant positive effect on the supporting environment of the industry and the development level of the construction industry.